Comparative Effect of Kawista Fruit (Limonia Acidissima) with Water and Concentration of Sodium Bicarbonate on The Quality of Carbonated Beverages - Alisha Shahnaz; Ida Agustini Saidi (jurnal makanan tropis dan teknologi agroindustri, 2020)
This research was aimed to study the effect of the comparison of wood apple (Limonia acidissima) with water and natrium bicarbonate concentrate on quality of carbonated beverage. The experiment was used Randomized Completely Block Design with two factors. First factor was the comparison of wood apple with water consisting 3 levels, they are K1 (wood apple 4 : water 5), K2 (wood apple 3 : water 5), and K3 (wood apple 2 : water 5). Second factor natrium bicarbonate concentrate consisting 3 levels, they are N1 (natrium bicarbonate 0,36%), N2 (natrium bicarbonate 0,42%), and N3 (natrium bicarbonate 0,48%). Data analysis using variance analysis and further test HSD 5%. The results indicate that there is no interaction between comparison of wood apple with water and natrium bicarbonate concentrate to all observation variable, yet treatment of natrium bicarbonate concentrate affected significantly to pH carbonated beverage. The best treatment was carbonated beverage of wood apple that was made using comparison of wood apple 2 with water 5 and natrium bicarbonate concentrate 0,42% which shows flavor organoleptic 3.80, color 4.87, aroma 4.07, sparkle 4.23, lightness (L*) 31.21, redness (a*) -2.95, yellowness (b*) 4.26, CO2 4.68 mg/ml, pH 3.91, lactic acid 0.75%, TPT 10.40Brix, and viscosity 0.95 mPa.s.